2022
DOI: 10.3390/md20070442
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Characteristics and Function of Phosphoglucomutase (PGM) in the Agar Biosynthesis and Carbon Flux in the Agarophyte Gracilariopsis lemaneiformis (Rhodophyta)

Abstract: Agar is widely applied across the food, pharmaceutical and biotechnology industries, owing to its various bioactive functions. To better understand the agar biosynthesis in commercial seaweed Gracilariopsis lemaneiformis, the activities of four enzymes participating in the agar biosynthesis were detected, and phosphoglucomutase (PGM) was confirmed as highly correlated with agar accumulation. Three genes of PGM (GlPGM1, GlPGM2 and GlPGM3) were identified from the G. lemaneiformis genome. The subcellular localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…According to researchers in the field, the transcription level of some agar biosynthesisrelated genes can indicate the agar content level. Chen verified that the enzyme activities of PGM and the agar content exhibited significant correlations (Pearson correlation coefficient: 0.896) after 7 days for G. lemaneiformis, under the nitrogen concentration treatment [33]. Most G. lemaneiformis strains in the high agar content group had higher transcription levels of galt than all strains in the low agar content group, which suggested that the galt gene played a crucial role in agar biosynthesis [34].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…According to researchers in the field, the transcription level of some agar biosynthesisrelated genes can indicate the agar content level. Chen verified that the enzyme activities of PGM and the agar content exhibited significant correlations (Pearson correlation coefficient: 0.896) after 7 days for G. lemaneiformis, under the nitrogen concentration treatment [33]. Most G. lemaneiformis strains in the high agar content group had higher transcription levels of galt than all strains in the low agar content group, which suggested that the galt gene played a crucial role in agar biosynthesis [34].…”
Section: Discussionmentioning
confidence: 80%
“…The normal distribution and the homogeneity of different datasets were confirmed by a Shapiro-Wilk test (p > 0.05) and Levene's test (p > 0.05), respectively. The one-way analysis of variance (ANOVA) was performed to determine the differences between the different datasets using Bonferroin's post hoc test and Tukey's post hoc test (Tukey HSD) [33]. If some datasets did not conform to the normal distribution, the Kruskal-Wallis test was used to analyse them [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation